Information Security and Cryptology - ICISC 2011 14th International Conference, Seoul, Korea, November 30 - December 2, 2011. Revised Selected Papers - Kim, Howon (Security and Cryptology ;, 2012)
This book constitutes the thoroughly refereed conference proceedings of the 14th International Conference on Information Security and Cryptology, held in Seoul, Korea, in November/December 2011. The 32 revised full papers presented were carefully selected from 126 submissions during two rounds of reviewing. The conference provides a forum for the presentation of new results in research, development, and applications in the field of information security and cryptology. The papers are organized in topical sections on hash function, side channel analysis, public key cryptography, network and mobile security, digital signature, cryptanalysis, efficient implementation, cryptographic application, and cryptographic protocol.